Overcoming challenges in healthcare interoperability regulatory compliance - Castanheira, António (2021)
There has been a significant increase in the quantity of information stored digitally by health institutions. Such information contains personal data from the actors in their universe. Thus, is crucial that it is governed by a set of rules, in order to allow it to be understood without losing important data. With the increased use of digital tools for storing and exchanging information, ethical issues began to arise in the context of the privacy of personal data. Questions about access, processing, treatment and storage of personal data became increasingly important in society, leading to the creation of the General Data Protection Regulation (GDPR) in force at European level. GDPR is one of the main challenges in healthcare interoperability regulatory compliance, therefore the proposed architecture shows an approach to enforce GDPR compliance into Agency for Integration, Diffusion and Archive Platform (AIDA), which is held by several healthcare unities in Portugal, using technologies like ElasticSearch and Kibana.